Mangrove dan Abrasi Pantai Kota Padang - Boby Rahman; Artika Zalni; Adisti Vadila; Eni Kamal; Abdul Razak; Widya Prarikelan; Mhd. Ridha (Journal of Innovative and Creativity, 2025)
Coastal erosion poses a serious threat to the coastal areas of Padang City, West Sumatra. The role of mangroves as natural protectors of the coast from erosion and tidal flooding is increasingly being eroded due to land conversion and human activities. This study aims to examine the relationship between mangrove damage and the level of erosion in several coastal areas of Padang and to evaluate the mitigation efforts that have been carried out. The research methods used were field surveys, remote sensing with satellite imagery, and analysis of coastal geomorphological data using the Digital Shoreline Analysis System (DSAS). The results of the study showed an increase in erosion in areas experiencing mangrove degradation, while areas with dense mangroves tended to experience accretion. The decline in mangrove area and quality is exacerbated by the conversion of areas into fish ponds and coastal development activities. Erosion mitigation needs to be carried out through mangrove rehabilitation and a participatory approach involving the community to maintain the sustainability of the ecosystem and environmental resilience of the Padang City coast.